2020
DOI: 10.2478/gp-2020-0021
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Associated Factors among International Students in a Private University of Bangladesh

Abstract: BackgroundDepression is the second major cause of disability and is a principal source of disease burden worldwide which is quite common among international students.AimThis study explored the depression and its associated factors among international students of a private university in Bangladesh.MethodsThis cross-sectional study was conducted among 149 international students at a private university in Dhaka, Bangladesh using the Center for Epidemiologic Studies Depression (CES-D 10) Scale.ResultsThe prevalenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 12 publications
2
15
0
Order By: Relevance
“…The survey questionnaire was adapted from similar research conducted in Bangladesh [ 4 ]. The online questionnaire had three parts—background information, challenges faced, and depression measurement.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The survey questionnaire was adapted from similar research conducted in Bangladesh [ 4 ]. The online questionnaire had three parts—background information, challenges faced, and depression measurement.…”
Section: Methodsmentioning
confidence: 99%
“…Nonetheless, IUSs face innumerable challenges when moving to a completely unknown non-native country [ 3 ]. Beyond the difficulties related to the educational institution, adjusting to a new place may present socialization stress among the students [ 3 , 4 ]. The IUSs encounter events and stressors beyond that of native students that have an impact on their mental health [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although gender plays a vital role in those infected with COVID-19, this important demographic factor has not been evaluated thoroughly with respect to acquiring COVID-19 infection in adolescents and young adults. Furthermore, it has been observed that there is an unmet need for psychological support for university undergraduates [ 11 , 12 , 20 ]. Thus, research on gender differences of COVID-19 psychological consequences and adherence to precautionary measures is urgently needed to understand the current scenario and to remedy the adverse consequences.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, concern regarding their education was causing a 25% increase in anxiety levels of the college students. In a similar study conducted in the neighboring nation of Bangladesh, students from universities reported a high level of anxiety and depression (Islam et al, 2020;Jamilah et al, 2020). It is also found that the level of distress is not dependent on the income of the family.…”
Section: Discussionmentioning
confidence: 85%